PERAN PENGUNGKAPAN ESG DALAM MENINGKATKAN TRANSPARANSI LAPORAN KEUANGAN - Amanda Putri Sri Rejeki Hutabarat; Nevanya Larasati Rusyanto; Nur Robya Azzahra; Novy Silvia Dewi (Jurnal Riset Multidisiplin Edukasi, 2026)
This study investigates the significance of Environmental, Social, and Governance (ESG) disclosure in amplifying the transparency of financial reporting within the corporate sector. Adopting a quantitative approach with a causal-comparative design, the research analyzes secondary data from 150 companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. The relationship between ESG disclosure scores and financial reporting transparency indices was examined using multiple linear regression analysis, integrating firm size, profitability, and leverage as control variables to isolate the primary effects. Empirical findings confirm that ESG disclosure exerts a positive and significant influence on financial reporting transparency. These results validate the propositions of legitimacy theory, signaling theory, and stakeholder theory, which posit that entities with high sustainability commitments tend to adopt a culture of radical transparency, thereby reducing information asymmetry in non-financial aspects while simultaneously enhancing the integrity of financial disclosures. Practically, this study emphasizes the urgency of standardized ESG reporting regulations to mitigate greenwashing risks and provides a strategic framework for management to strengthen corporate credibility and investor confidence in the capital market.